2018
DOI: 10.1002/gcc.22542
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of BCOR gene mutation as a prognostic factor in acute myeloid leukemia with intermediate cytogenetic prognosis

Abstract: BCOR gene is a transcription regulatory factor that plays an essential role in normal hematopoiesis. The wider introduction of next-generation sequencing technology has led to reports in recent years of mutations in the BCOR gene in acute myeloid leukemia (AML), but the related clinical characteristics and prognosis are not sufficiently understood. We investigated the clinical characteristics and prognosis of 377 de novo AML cases with BCOR or BCORL1 mutation. BCOR or BCORL1 gene mutations were found in 28 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…In 2011, we discovered recurrent loss-of-function mutations of BCOR in AML (about 4% of cases with normal karyotype) and found that they were usually mutually exclusive of FLT3-ITD and NPM1 mutations, co-occurred with DNA methyl transferase (DNMT3A) mutations and were associated with a poor outcome [9]. Our findings have been subsequently confirmed by other investigators both in AML and MDS [10][11][12][13][14]. Interestingly, one study on Japanese patients reported a preferential co-occurrence of BCOR mutations with K-RAS, N-RAS, and RUNX1 mutations [11].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In 2011, we discovered recurrent loss-of-function mutations of BCOR in AML (about 4% of cases with normal karyotype) and found that they were usually mutually exclusive of FLT3-ITD and NPM1 mutations, co-occurred with DNA methyl transferase (DNMT3A) mutations and were associated with a poor outcome [9]. Our findings have been subsequently confirmed by other investigators both in AML and MDS [10][11][12][13][14]. Interestingly, one study on Japanese patients reported a preferential co-occurrence of BCOR mutations with K-RAS, N-RAS, and RUNX1 mutations [11].…”
Section: Introductionsupporting
confidence: 65%
“…Interestingly, one study on Japanese patients reported a preferential co-occurrence of BCOR mutations with K-RAS, N-RAS, and RUNX1 mutations [11]. BCOR 1 ligand (BCORL1) gene has been also found to be mutated in 3.7-6% of AML patients [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Uniquely, our patient had resolution of his previous BCOR, RUNX1, and IDH2 mutations on the NGS panel. BCOR and RUNX1 mutations are both adverse prognostic markers and are associated with higher risk disease in AML, whereas IDH2 mutations are generally thought to have a neutral impact but have become more clinically relevant recently with the discovery of novel IDH1/2 inhibitors [16][17][18]. To our knowledge, resolution of BCOR, RUNX1, or IDH2 mutations has not been described in previous case reports of SR in AML; however, monitoring of RUNX1 and IDH2 mutation status by NGS during CR has been shown to identify patients at risk of relapse [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…NGS techniques allow for the identification of new molecular subgroups potentially related to specific clinical characteristics, in addition to those already identifiable by cytogenetic studies. In the context of these specific entities, association with BCOR comutations (Table 2) is particularly relevant in the following instances: intermediate cytogenetic prognosis and FLT3–ITD-negative AML in adult patients under 65 [89], nonselected myeloid neoplasms with mutations in cohesin-coding genes [95], AML with changes associated with myelodysplasia [92], AML with trisomy 11 or 13 [99,100], AML with balanced or unbalanced chromosomal rearrangements [97], AML with normal karyotype [97,98,107] (in particular, pediatric AML) [88] or if co-occurring mutations in NPM1, CEBPA, FLT3-ITD, MLL-PTD or RUNX1 are present [105,107,117].…”
Section: Hemolymphopoietic System Neoplasmsmentioning
confidence: 99%